0579 Non Intrusive and Unattended Sleep Analyzer Effectively Screens Patients Suspected of Sleep Apnea: A Comparison With Polysomnography. (27th May 2020) - Edouard, P; Campo, D; Bartet, P; Marais, L; Petitjean, M; Roisman, G; Bruyneel, M; Escourrou, P
Abstract: Introduction: Sleep Apnea Syndrome (SAS) is largely underdiagnosed due to the cost and availability of Polysomnography (PSG). We aimed at evaluating the diagnosis of SAS with the WITHINGS Sleep Apnea Detector (SAD), a non-intrusive pressure and sound sensor placed under the mattress. Methods: 118 patients (67 F, 49 years, BMI 33kg/m²) suspected of SAS had an in-laboratory PSG together with Sleep Apnea Detector. From the pressure signal, Sleep Apnea Detector derives respiratory and cardiac signals and movements. From the microphone, snoring and snorting are detected. These features are used to detect sleep periods with a Random Forest classifier and apnea and hypopnea events with a Convolutional Neural Network. The Total Sleep Time (TST) and Apnea Hypopnea Index (AHI) deduced (TSTsad, AHIsad ) are compared with the PSG results scored according to AASM rules (TSTpsg, AHIpsg ). AHI and TST were compared using bias and Mean Absolute Error (MAE). Sensitivity, specificity, likelihood ratios (LR) and AUROC were calculated for AHI thresholds of 15 and 30/hr. Results: The average (SD) TSTpsg was 367 (61) minutes. Sleep Apnea Detector overestimated TST by 25 minutes, 7.0% of the average duration in the sample. The precision is acceptable, with a MAE=53 minutes. Average AHIpsg was 32.5 (30.1) and AHIsad 32.8 (29.9). The bias was 0.3 (95% CI [-2.7, 3.3]), MAE=10.3. The sensitivity (Se15 ) and specificity (Sp15 ) and their 95% confidence intervals were Se15 =88.0% [79.0, 94.1] and Sp15 =88.6% [73.3, 96.8]. Positive and negative LR were respectively LR + 15 =7.70 and LR - 15 =0.136. AUROC15 =0.926. At the 30 threshold, Se30 =86.0% [73.3, 94.2] and Sp30 =91.2% [81.8, 96.7]. Positive and negative LR were LR + 30 =9.75 and LR - 30 =0.153. AUROC30 =0.954. Conclusion: Sleep Apnea Detector has excellent sensitivity and specificity, low bias and good precision. Thus it can be used as an unattended SAS screening device in patients likely to suffer from SAS. Support: WITHINGS